Strategies to improve the potential of transdermal devices by enhancing the skin permeation of therapeutic entities - Nair, Syam S. (Journal of Drug Delivery and Therapeutics, 2019)
Although transdermal route of drug delivery displays numerous benefits over conventional strategies, this pathway is yet to presents its complete potential. The chief ground for this statement is ascribed to the presence of extremely packed outermost layer of skin called stratum corneum. This compactly packed barrier is selectively permeable and furnishes smaller and lipophilic molecules to diffuse into the deeper skin layers. Due to this only a few transdermal product is commercially available. So in order to guarantee the effective transport of drug molecules, it is necessary to break the stratum corneum layer. There are two acceptable methods to break the stratum corneum architecture- active strategy which comprises the application of external energy such as in electroporation, sonophoresis, iontophoresis etc. and passive strategy which involve the application of permeation enhancers, nanoparticles etc. This article comprehensively detail the active and passive methods employed in transdermal drug delivery systems to disrupt the stratum corneum bilayers. Keywords: transdermal drug delivery, lipophilic molecules, permeation enhancers